2017
DOI: 10.1128/jvi.00827-17
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol 25-Hydroxylase Inhibits Porcine Reproductive and Respiratory Syndrome Virus Replication through Enzyme Activity-Dependent and -Independent Mechanisms

Abstract: Cholesterol 25-hydroxylase (CH25H) has recently been identified as a host restriction factor that exerts antiviral effects by catalyzing the production of 25-hydroxycholesterol (25HC). CH25H can be rapidly induced upon infection with some viruses. Porcine reproductive and respiratory syndrome virus (PRRSV), an arterivirus, has ranked among the most important swine pathogens since it was discovered in the late 1980s. In this study, we found that PRRSV infection significantly downregulated the expression of CH25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 77 publications
1
62
0
Order By: Relevance
“…Previous studies have indicated that CH25H has an antiviral effect against some viruses and generates antiviral activities through the production of 25HC. For example, CH25H restricts HCV replication through the obstruction of membranous web formation (Anggakusuma et al, 2015); CH25H inhibits PRV by blocking viral attachment and internalization ; 25HC reduces PRRSV infection by inhibiting viral penetration but does not affect adsorption, replication, or release of PRRSV (Ke et al, 2017); and 25HC suppresses Lassa virus infection through aberrant GP1 glycosylation (Shrivastava-Ranjan et al, 2016). In the present study, the overexpression of CH25H or 25HC inhibited PEDV infection by impeding virion entry, which is similar to that observed in PRRSV.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have indicated that CH25H has an antiviral effect against some viruses and generates antiviral activities through the production of 25HC. For example, CH25H restricts HCV replication through the obstruction of membranous web formation (Anggakusuma et al, 2015); CH25H inhibits PRV by blocking viral attachment and internalization ; 25HC reduces PRRSV infection by inhibiting viral penetration but does not affect adsorption, replication, or release of PRRSV (Ke et al, 2017); and 25HC suppresses Lassa virus infection through aberrant GP1 glycosylation (Shrivastava-Ranjan et al, 2016). In the present study, the overexpression of CH25H or 25HC inhibited PEDV infection by impeding virion entry, which is similar to that observed in PRRSV.…”
Section: Discussionsupporting
confidence: 77%
“…PRRs include host restriction factors, many of which are simulated by interferon, which directly or indirectly target multiple stages of the viral life cycle. For instance, the membrane-associated enzyme, cholesterol 25-hydroxylase, inhibits viral entry and degrades viral proteins (Evans et al, 2017;Ke et al, 2017). Moreover, viperin (an IFN-stimulated gene) suppresses HCMV infection by inhibiting viral structural protein synthesis, assembly, and maturation (Chin and Cresswell, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Primers (Table 2) were designed using the Primer Express software (version 3.0; Applied Biosystems, Carlsbad, CA). Absolute quantitative mRNA levels were calculated using standard curves as previously described [50].…”
Section: Quantitative Rt-pcr (Qpcr)mentioning
confidence: 99%
“…To investigate the role of endogenous TRIM22 on PRRSV replication, MARC-145 cells were treated with control-siRNA or si-TRIM22 followed by PRRSV infection, then viral titers were measured by TCID 50 , and viral total RNA were quantified by qPCR at 36 hpi. Compared to control cells, we observed that there was a statistically significant increase of the virus yields in the supernatants of si-TRIM22-transfected cells (Fig.…”
Section: Knockdown Of Trim22 Augmented the Replication Of Prrsvmentioning
confidence: 99%
See 1 more Smart Citation